The Challenges of Big Data Analytics in the Mobile Communications Sector - Saldžiūnas, Kęstutis; Skyrius, Rimvydas (Ekonomika, 2017)
The activities of the MNO (Mobile Network Operator) feature rapid development and business model innovations; one of their principal results is the communications infrastructure that is vital for economic growth. This dynamic and changing mode of operation (modus operandi) introduces high requirements for business decisions and overall informing to maintain competitiveness. One of the principal success factors in MNO activities is the application of contemporary information technologies, in particular technologies of business intelligence and analytics.The activities of MNO create large data volumes, leading to a significant potential discovery of insights from data. As a result, MNOs have been using analytical technologies to mine large data volumes for several decades, and experience accumulation started long before the term “big data” emerged in academia and business. The growing dynamics of activities drive the efficient use of analytical experience to boost competitive advantage. The goal of this paper is to define the most important features of the use of big data analytics in MNO business and any possible related challenges.
Keywords: mobile network operators; analytical technologies; big data analytics